FADE TO WHITE OR STEREOTYPE: PATRIARCHAL POLICING OF GENDER NORMS IN TELEVISION AND FILMIC REPRESENTATIONS OF CHILDBIRTH - Nall, Jeffrey Allen (Gender Questions, 2016)
Drawing on the examination of five feature films, including Twilight: Breaking Dawn – Part 1, and more than half-a-dozen popular television programmes, including Parenthood, The L Word and The Secret Life of the American Teenager, this work argues that dominant cultural representations foster a narrow and potentially damaging, disempowering and dehumanising depiction of childbirth. Together these works foster a dominant conceptualisation and representation of childbirth that narrowly represents childbirth, emphasising themes including ‘bitter birth’ or birth as affliction, a reproductive double bind affirming women’s fundamental procreative role while also pathologising their reproductive processes, and the trivialisation of women’s birthing agency through the broad failure to recognize maternal magnificence. This work further argues that dominant representations of maternity pervading mass media, as indicated in the examined examples, normalise patriarchal gender roles, particularly emphasised femininity, and mark gender noncomformists as deviant. The promotion of such norms is clear in contemporary cultural depictions of childbirth, including birth-related hit films such as Knocked Up and The Back-up Plan. In the last of these an important component of patriarchal gender codes is further shown to include heteronormativity.